GAMBARAN KRISTAL HEMOGLOBIN PADA BERCAK DARAH YANG TERPAPAR BEBERAPA ZAT PEMBERSIH LANTAI DOMESTIK BERBAHAN KARBOL - Sherly Nurfadhila; Enikarmila "; M. Tegar Indrayana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Bloodstains on the floor, clothes and on the weapon used for crime are most likely to be cleaned of by the criminal as part of the attempt to vanish the evidence. Abolition of the bloodstains on the floor can use carbolic floor cleaner. Carbolic floor cleaner contamination on bloodstains may affect the result of bloodstains identification using Teichmann and Takayama tests. The purpose of this research were to know the description of hemoglobin crystal as a result of Teichmann and Takayama test on bloodstains exposed by carbolic floor cleaner. This descriptive research was done at Biochemical Laboratory of Medical Faculty Riau University. Eight carbolic floor cleaner solutions were used in this research. Each carbolic floor cleaner were wiped on each slide using a tissue, then Teichmann and Takayama test were done on each slide. The results of this study shows that the bloodstains exposed by carbolic floor cleaner will still form hemin crystals in Teichmann test and hemokromogen crystal in Takayama test. This research emerged allegations that carbol exposure was not able to inhibit the formation of hemoglobin crystals and does not damage the heme structure of hemoglobin.Keywords : bloodstain, carbolic acid, Teichmann test, Takayama test